Penentuan Modulus Geser Tanah Menggunakan Metode Analisis Multi-channel Gelombang Permukaan - Ariestianty, Susy K; Taha, Mohd Raihan; Anuar, Khairul; Nayan, Mohd; Chik, Zamri (Jurnal Semesta Teknika, 2009)
Multi-channel Analysis of Surface Wave (MASW) is one of non-destructive seismic methods that can be used to obtain the soil dynamic parameters, such as the shear wave velocity (VS) and the shear modulus (G). Indirect measurement of soil dynamic parameters can also be estimated by the empirical correlations of VS/G and NSPT values obtained from Standard Penetration Test (SPT). However, borehole test is required for SPT, which is relatively high cost and also may disturb in surrounding environment of investigated sites. Therefore, MASW seismic method then can be performed as alternative options in avoiding these problems. In this study MASW method was used to obtain the VS and G profile at several selected sites in Peninsular of Malaysia, i.e., Universiti Kebangsaan Malaysia Bangi campus, Selangor and Sungai Temala, Terengganu. The Rayleigh wave propagations are recorded using 24 geophones of 4.5 Hz resonant frequency connected to the seismograph. Subsequently, the seismic data is processed and analyzed to generate the VS profile versus depth in one-dimensional (1-D) and two-dimensional (2-D) form. In general, the shear wave velocity from MASW method measurements show reasonable agreements compared to the VS values obtained from empirical correlation of NSPT value. A good relationship between shear modulus from this study compared to empirical correlations of NSPT value from previous researchers. Finally, MASW method can be nondestructively used for identifying and validating subsurface soil condition of the investigated sites.